2018
DOI: 10.1002/jrs.5350
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Raman scattering signal using photonic nanojet of portable and reusable single microstructures

Abstract: We report the enhancement of Raman scattering signal for the first time using photonic nanojet of a lollipop‐shaped microstructure (LMS) fabricated with the help of a nanosecond CO2 laser. The LMS consists of a dielectric microsphere attached to a long stem/tapered fiber. The enhancement was achieved by focusing the incident laser light on sample surface through the microsphere of LMS. The experimentally observed enhancement was found to be comparable with that obtained from commercial microspheres that are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…We believe the primary reason for the enhancement is the presence of the strongly localized electric field inside of the photonic nanojet on the shadow side of the sphere, as noted in other research, which leads to stronger Raman scattering. However, the influence of the NA is present, and there is a possibility that part of the mechanism is the increase of the NA, where the sphere allows better collection of scattered light, but further research is needed.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…We believe the primary reason for the enhancement is the presence of the strongly localized electric field inside of the photonic nanojet on the shadow side of the sphere, as noted in other research, which leads to stronger Raman scattering. However, the influence of the NA is present, and there is a possibility that part of the mechanism is the increase of the NA, where the sphere allows better collection of scattered light, but further research is needed.…”
Section: Resultssupporting
confidence: 61%
“…Geometrical aspects have been mostly investigated in terms of microsphere size and objective that has been used . Several researchers have achieved the highest enhancement positioning the focus of the incident beam so that the width of the beam covered the sphere . Alessandri et al have shown that the lower the numerical aperture (NA) of the objective is used, the higher the relative enhancement, while the incident beam was focused on top of the microsphere.…”
Section: Introductionmentioning
confidence: 99%
“…Arya and co‐workers described the enhancement of Raman scattering intensity using a photonic nanojet of portable and reusable single lollipop‐shapted microstructures. These lollipop‐shapted microstructures are extremely useful for enhancing the Raman scattering and fluorescence signals of single or few molecules . Chen et al report a statistical analysis of cuboctahedral silver nanocrystals in Langmuir–Blodgett film SERS substrates.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…These lollipop-shapted microstructures are extremely useful for enhancing the Raman scattering and fluorescence signals of single or few molecules. [108] Chen et al report a statistical analysis of cuboctahedral silver nanocrystals in Langmuir-Blodgett film SERS substrates. Their results help to identify important SERS substrate characteristics that influence the performance of a SERS substrate.…”
Section: Carbon Nanotubes Carbon Materials Graphene Layered Solimentioning
confidence: 99%
“…The generated photonic nanojet often has a sub-wavelength and high-intensity focus spot with a long effective length. Thus, the photonic nanojets are applied in several optical and photonic applications, including super-resolution white-light nanoscopy [22], optical waveguide [23], enhancement of Raman scattering signals [24,25,26,27,28,29], optical nano-patterning [30], detection of single nanoparticle and biomolecules [31], enhancement of backscattering of light [32], optical data-storage [33], optical forces [34], optical super-resolution photoacoustic microscopy [35], laser surgery [36], and photon fluorescence enhancement [37].…”
Section: Introductionmentioning
confidence: 99%